2004
DOI: 10.1002/j.1556-6678.2004.tb00285.x
|View full text |Cite
|
Sign up to set email alerts
|

A Ten‐Year Longitudinal Study of the Career Development of Students: Summary Findings

Abstract: This article summarizes the principal findings of a 10-year longitudinal study of the career development experienced by a sample of students. Beginning with 208 second graders, data were collected 6 times, concluding when the students were in the 12th grade. Principal variables measured included occupational aspirations and expectations, gender role beliefs, out-of-school activities, parental involvement in career awareness, and work experience. Concepts from L. Gottfredson's (1981) circumscription theory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 28 publications
2
35
0
3
Order By: Relevance
“…The adult sample participants were asked to think back to their high school experience (5 years earlier) in terms of several career development issues. Just as they did as seniors in high school, these adults also indicated that high school teachers were influential in their career development (Helwig, 2004). In fact, 4 indicated that the primary career influence came from a high school teacher.…”
Section: Discussionmentioning
confidence: 96%
“…The adult sample participants were asked to think back to their high school experience (5 years earlier) in terms of several career development issues. Just as they did as seniors in high school, these adults also indicated that high school teachers were influential in their career development (Helwig, 2004). In fact, 4 indicated that the primary career influence came from a high school teacher.…”
Section: Discussionmentioning
confidence: 96%
“…Se puede decir que estos datos refuerzan estudios previos sobre el papel del profesorado en el desarrollo de la carrera de los estudiantes (p.e., Abreu, 1996Abreu, , 2001Bright, Pryor, Wilkenfeld y Earl, 2005;Ferreira, Nascimento y Fontaine, 2009;Helwig, 2004Helwig, , 2008Núñez del Río y Abad, 2009;Pinto, Taveira y Fernandes, 2003), destacando el carácter más o menos deliberado y más o menos intencional de la acción de estos profesionales y también la acción directa o indirecta de los mismos.…”
Section: Discussionunclassified
“…Por otro lado, la influencia de los docentes puede ser indirecta, mediada por otras variables como el rendimiento académico y el currículo (Bojuwoye y Mbanjwa, 2006;Jackson, Kacanski, Rust y Beck, 2006;Sax y Bryant, 2006). El ambiente escolar, el currículo, los niveles de desempeño académico, las expectativas de los maestros y la relación pedagógica, se relacionan con la toma de decisiones, las aspiraciones y las creencias (Cortés, 2009;Helwig, 2004Helwig, , 2008Kuijpers, Meijers y Gundy, 2011;Pinto, Taveira y Fernandes, 2003;Sax y Bryant, 2006;Tien, Wang y Liu, 2009). …”
Section: Introductionunclassified
See 1 more Smart Citation
“…It seems that children as young as age 4 report sex-based occupational preferences (Trice & Rush, 1995). Fantasy aspirations for girls compared to boys increased more proportionally from second grade (10% more) to 12th grade (20% more) (Helwig, 1998a(Helwig, ,b, 2001(Helwig, , 2004. Females were more likely to have high-and lowprestige aspirations, whereas males were more likely to aspire to moderate-prestige jobs (see Rajewski, 2005).…”
Section: Occupational Aspirationsmentioning
confidence: 99%